Effects of multimodal nursing intervention with health education on recovery, pain, and psychological outcomes after laparoscopic cholecystectomy: a retrospective cohort study - Hu, Zhongfang; Liu, Huan (Frontiers in Surgery, 2026)
ObjectiveTo explore the effects of multimodal nursing intervention combined with health education on postoperative recovery, pain management, and psychological state in patients undergoing laparoscopic cholecystectomy.MethodsThe clinical data of 100 patients who underwent laparoscopic cholecystectomy in our hospital from January 2023 to December 2024 were retrospectively analyzed. The patients were divided into a control group (CG, n = 50, routine care) and an intervention group (IG, n = 50, multimodal nursing intervention combined with health education) according to the nursing method. The two groups were compared in terms of postoperative recovery indicators, pain scores, psychological state, immune function indicators, incidence of complications, and functional recovery scores.ResultsThe IG demonstrated significantly shorter time to first flatus, first defecation, first ambulation, hospital stay, and incision healing than the CG (P < 0.05). VAS scores were significantly lower in the IG at all postoperative time points (P < 0.05). SAS and SDS scores were significantly lower in the IG at discharge (P < 0.05). The IG displayed higher CD4+ level than the CG at discharge (P < 0.05). The IG exhibited significantly lower incidence of abdominal distension and total incidence of postoperative complications than the CG (P < 0.05). The scores of daily activities, self-care ability, pain control, and overall recovery in the IG were significantly higher than those in the CG (P < 0.05).ConclusionMultimodal nursing intervention combined with health education can significantly promote postoperative recovery of patients undergoing laparoscopic cholecystectomy, effectively control postoperative pain, improve psychological state and immune function, reduce the incidence of complications, and improve the quality of functional recovery.